Pelatihan Menggambar Ilustrasi Cerita Rakyat untuk Pengembangan Karakter Anak-Anak Sekolah Dasar di Bali - Krisna Ari, Ida Ayu Dwita; Nuriarta, I Wayan (Bakti Budaya: Jurnal Pengabdian kepada masyarakat, 2023)
Mesatua folklore in Bali has moral education values. The aim of this training is to draw folklore illustrations for elementary school (SD) children in Bali to preserve the mesatua tradition whose values ​​are relevant to society. This training program uses three program approaches, namely (1) Mesatua, (2) Drawing illustrations, (3) Reading children's drawings. The implementation of the program resulted in the provision of mesatua folklore in each region which was given differently according to the needs of the local environment. At the public elementary school in Budakeling village, Karangasem district, they were given the folklore I Belog, while at the public elementary school in Tukadsumaga village, Buleleng district, they were given the story The Arrogant Frog. The conclusion shows that children's illustrative work discussed line, composition, illustration, typography and color. The works produced by elementary school children in the two districts show works that are honest, expressive and free. The composition of the fields also shows that their drawings are full of freedom and confidence in drawing. Character values ​​such as not being arrogant, having to study hard and being obedient to worship are contained in the children's drawings. ==== Cerita rakyat mesatua di Bali memiliki nilai pendidikan moral. Tujuan pelatihan menggambar ilustrasi cerita rakyat untuk anak-anak Sekolah Dasar (SD) di Bali adalah untuk melestarikan tradisi mesatua yang nilai-nilainya relevan dengan masyarakat. Program pelatihan ini menggunakan tiga pendekatan program, yaitu (1) mesatua, (2) menggambar ilustrasi, dan (3) membaca gambar anak. Pelaksanaan program menghasilkan pemberian cerita rakyat mesatua di masing-masing daerah diberikan secara berbeda-beda sesuai dengan kebutuhan lingkungan setempat. Di SD Negeri Desa Budakeling, Kabupaten Karangasem diberikan cerita rakyat I Belog, di SD Negeri Desa Tukadsumaga, Kabupaten Buleleng diberikan cerita Si Kodok Sombong. Simpulannya menunjukkan bahwa karya ilustrasi anak-anak dibahas garis, komposisi, ilustrasi, tipografi, dan warna. Karya-karya yang dihasilkan oleh anak-anak SD di dua kabupaten menunjukkan karya yang jujur, ekspresif, dan bebas. Komposisi bidangnya pun menunjukkan gambar mereka penuh kebebasan dan rasa percaya diri dalam menggambar. Nilai-nilai karakter seperti tidak boleh sombong, harus rajin belajar, serta taat beribadah terkandung dalam gambar anak.